'Best practice' human resource management : perfect opportunity of dangerous illusion? - Marchington, Mick (2000)
Notes that as a result of work done in the UK and USA it has been asserted that a particular bundle of HR practices can increase profits irrespective of organizational industrial or national context. Focuses on the way in which HRM is characterized in these writings, queries whether the practices which are typically assumed and put forward as 'good' may not appear quite as beneficial to workers when analysed more systematically. Suggests that there are a number of problems with the notion of 'best practice', both in relation to the meaning of specific practices, and their consistency with each other, and the claims that this version of HRM is universally applicable. Exposes the unitarist underpinnings of this literature.